2017
DOI: 10.3390/catal7010032
|View full text |Cite
|
Sign up to set email alerts
|

A Short Review on the Catalytic Activity of Hydrotalcite-Derived Materials for Dry Reforming of Methane

Abstract: Nickel-containing hydrotalcite-derived materials have been recently proposed as promising materials for methane dry reforming (DRM). Based on a literature review and on the experience of the authors, this review focuses on presenting past and recent achievements on increasing activity and stability of hydrotalcite-based materials for DRM. The use of different NiMgAl and NiAl hydrotalcite (HT) precursors, various methods for nickel introduction into HT structure, calcination conditions and promoters are discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(49 citation statements)
references
References 90 publications
(150 reference statements)
1
46
0
2
Order By: Relevance
“…x+ (A n− ) x/n •mH 2 O, where M II and M III are divalent and trivalent cations of metals, respectively, A n− is an n-valent anion and m is the number of molecular water [6,7]. In this structure, the Mg 2+ cations are partially substituted by Al 3+ cations resulting in a positive charge.…”
Section: Introductionmentioning
confidence: 99%
“…x+ (A n− ) x/n •mH 2 O, where M II and M III are divalent and trivalent cations of metals, respectively, A n− is an n-valent anion and m is the number of molecular water [6,7]. In this structure, the Mg 2+ cations are partially substituted by Al 3+ cations resulting in a positive charge.…”
Section: Introductionmentioning
confidence: 99%
“…Thermodynamic modelling demonstrated that theoretically H2 could be produced at about 100 º C and CO at about 300 º C by the low-temperature activation of CH4 and CO2 66 shifted their study to focus on nickel-based catalysts by choosing different support and doping different promoters to enhance its catalytic performance 67, [73][74][75][76] . Table 3 summarizes the recently reported Ni-based catalysts at temperatures below 500 º C. It can be seen that the lowest operating temperature was 400 º C, but poorer CH4 and CO2 conversions were achieved compared to those experiments carried out at high temperatures,…”
Section: Dry Reforming Of Methanementioning
confidence: 99%
“…It was found that the RDS is H 2 O + *O → *OOH + H + + e − , but that the RDS and the overpotential are dependent on the doping metal, which opens the possibility of improved doped nickel layered hydroxide OER catalysts. Other reviewed fields in which HTs are used as catalysts are biodiesel production, where their base properties are used, H 2 production, nitrogen oxide abatement, catalytic oxidation of alcohols, dry reforming of methane and other reactions relevant for the environment protection . It should be noted, however, that the HT is often used just as the precursor of the effective catalyst.…”
Section: D Nanostructured Oxide Filmsmentioning
confidence: 99%